PENERAPAN PENDEKATAN HEURISTIK DALAM MENINGKATKAN HASIL BELAJAR IPA PESERTA DIDIK DI MADRASAH IBTIDAIYAH - Laila Mutiara Sari; Rahmayati Fitria Purba; Rizki Umayroh; Siti Munawaroh; Rizki Akmalia (Fakultas Keguruan dan Ilmu Pendidikan, 2022)
This article was written with the aim of knowing how to apply the heuristic approach to improve student learning outcomes at the elementary level/Madrasah Ibtidaiyah, especially in Natural Science subjects. This study uses a qualitative method, namely by conducting a literature review. The author collects data and information from trusted journals and books for the truth and in accordance with the discussion of this article. With this paper, it is hoped that science subject teachers in particular to be able to apply this heuristic approach because it is believed that various research results and various other literatures can consistently improve student learning outcomes.